2019
DOI: 10.9745/ghsp-d-18-00241
|View full text |Cite
|
Sign up to set email alerts
|

Cell Phone Counseling Improves Retention of Mothers With HIV Infection in Care and Infant HIV Testing in Kisumu, Kenya: A Randomized Controlled Study

Abstract: Tailored, one-on-one counseling delivered via cell phone was very effective in retaining mothers with HIV in care and in promoting infant HIV testing and antenatal and postnatal care attendance. The highest risk of loss to follow-up among women with HIV accessing PMTCT services was prior to delivery and then after infant HIV testing at 6 weeks. Challenges include continued limited access to cell phones, difficulty with reaching participants on the phone, and poor adherence to antiretroviral therapy for a subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 27 publications
0
49
0
Order By: Relevance
“…Studies in Kenya, Uganda, India, Tanzania and Botswana reported that some participants were concerned about unwanted HIV disclosure, others reported anticipated stigma arising from SMS content, which may mention the words medication and HIV. 10 , 16 , 17 A systematic review showed that unreliable internet connections and high purchase and maintenance costs of smart phones resulted in unsuccessful mHealth interventions in resource-limited settings. 18 Others have also reported logistical challenges; including the fact that family members often share mobile phones, the unreliable access to electricity, and issues of mobile phones breaking.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Kenya, Uganda, India, Tanzania and Botswana reported that some participants were concerned about unwanted HIV disclosure, others reported anticipated stigma arising from SMS content, which may mention the words medication and HIV. 10 , 16 , 17 A systematic review showed that unreliable internet connections and high purchase and maintenance costs of smart phones resulted in unsuccessful mHealth interventions in resource-limited settings. 18 Others have also reported logistical challenges; including the fact that family members often share mobile phones, the unreliable access to electricity, and issues of mobile phones breaking.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is also supported by literature that suggests case workers are more effective when they have access to all resources essential to basic care. 20 , 21 Adequate care resources and comprehensive care plans have also been shown to be important for treatment program effectiveness for people living with HIV. 11 , 20 , 41 Program funders could consider expanding HIV program budgets to account for activista reimbursement for transportation and airtime (i.e., cell phone service used for case management).…”
Section: Discussionmentioning
confidence: 99%
“…Literature highlights the importance of case worker connectedness to share challenges 5 , 6 , 14 , 15 and of connections to additional services to ensure that beneficiaries receive comprehensive, whole-person care. 9 , 18 , 20 , 21 , 42 The influence of care team networking and referral networks is an important area for future research. Similarly, since CBOs all followed similar protocols for case management, the influence of specific care methods could not be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations